Epidemiological characteristics of accidental needle-stick injury among health care professionals in primary healthcare in Zenica - Suad Sivić; Larisa Gavran; Aida Baručija; Alma Alić (Medicinski glasnik, 2019)
Aim: To determine the extent and characteristics of incidental injuries, primarily by needles and other medically sharp instruments and to recommend preventative activities to health care professionals. Methods: The survey was conducted among 200 healthcare and non-healthcare employees of the Primary Health Care Centre Zenica (48% of the total number of employees). Care workers were surveyed, and the sample was randomly selected in proportion to the number of employees in institutional departments. Respondents answered questions about gender and age, work experience and qualifications; the number and type of exposure to incidents in the past year, number of career incidents, number of reported incidents; information on the manner and cause of the incident. Results: The sample consisted mainly of females, 153 (83.2%). An exposure to incident during their work was experienced by 128 (69.6%) respondents: needle-stick injury, 79 (42.9%), unforeseen patient response, 42 (22.8%), rush to perform the procedure, 34 (18,5%), and negligence, 18 (9.8%). The incidents most frequently occurred in gynaecology department (all respondents experienced an incident event), followed by department of family medicine, 47 (67%). The main reason for these incidents was rush to perform procedures, in 9 (12.5%). Of 128 experienced incident events, 21 (16.4%) were reported. Conclusion: The low rate of reporting of exposure to incidents does not provide a realistic basis for risk assessment and preventive action. Primary task for improving safety of work processes at our setting will be to raise employee's awareness of the need to report exposure incidents.
Keywords: prevention and control; risk assessment; risk factors